Changes in soil characteristics and estimated cost on reclamation of former sand mining land - Muhammad Nur Fauzan; Rini Dwiastuti; Sujarwo Sujarwo; Syahrul Kurniawan (Brawijaya University, 2022)
The utilization of natural resources in recent decades is not accompanied by proper and effective management. This has a major impact on environmental degradation in watershed scale and climate change. The study aimed to evaluate changes in soil characteristics at various ages of sand mining and the cost of reclamation of environmental degradation due to sand mining activities. The study was conducted in Sumberbulu Micro Watershed, which is located in Wajak Sub-District, Malang Regency. Soil sampling was collected from un-mined, 2 to 6 years old sand mining and post-mining lands. Natural resource equivalency analysis (REA) was applied for environmental damage assessment and reclamation cost calculation required to restore natural resource services to their original condition. The findings show that sand mining activities significantly decreased soil organic C in 0-40 cm soil depth, resulting in increased soil bulk density and decreased soil porosity at 20-40 cm depth of soil. Sand mining activities by using truck traffic carrying mining products, soil erosion, and the removal of topsoil during mining activities determined changes in soil properties. REA shows that the total area of land that must be reclaimed is 21,487 ha. The land will be reclaimed by revegetation (with maize) to restore the lost function of environmental services and income of local farmers, assuming a reclamation cost of 36,767,500 IDR/ha. Therefore, post-mining land reclamation should be encouraged by the government for mining business actors in Indonesia so that the land can be reused as before.